Influence of Tribochemical Reaction on Friction and Wear Behavior of Metallic Materials in n-Hexane and in Ethanol - Yuko Hibi (Japanese Society of Tribologists, 2016)
Cast iron, aluminum metal and sintered aluminum-silicon (Al-Si) were slid against SUS440C stainless steel in n-hexane and in ethanol. In the case of the cast iron/stainless steel and aluminum metal/stainless steel pairs, friction and wear were lower in n-hexane than in ethanol. In contrast, the friction and wear for the sintered Al-Si/stainless steel pair were much higher in n-hexane than in ethanol. The results from morphological observations and chemical analyses of the worn surfaces suggested that the wear mechanism was influenced by the physical properties of the sliding materials and the tribochemical reactions between the sliding materials and lubricants.